1988
DOI: 10.1021/ja00218a008
|View full text |Cite
|
Sign up to set email alerts
|

Surface derivatization and isolation of semiconductor cluster molecules

Abstract: x J. If this energy is converted completely into visible photons (energy-4 X J), the total number of photons is 7 X 10-14/4 X-2 X lo5. Taking account of the light collection efficiency (-0.004), the number of photons collected per diode array channel is-0.8, which could hardly be detected. Considering also the efficiency of energy conversion from discharge to emission, the energy consumed for the excitation of TSE should be several orders of magnitude higher than E estimated above. Namely, most of the electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
382
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(391 citation statements)
references
References 5 publications
6
382
0
3
Order By: Relevance
“…22 Those diameters of CdS nanoparticles agreed with the expected diameter of "water pool" in the reversed micelle. 6,23 Thus, we have confirmed that the size of particles can be controlled easily by changing the […”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…22 Those diameters of CdS nanoparticles agreed with the expected diameter of "water pool" in the reversed micelle. 6,23 Thus, we have confirmed that the size of particles can be controlled easily by changing the […”
Section: Resultsmentioning
confidence: 53%
“…CdS nanoparticles were prepared in reversed micelles following the method of Steigerwald et al 6 The preparation was operated under argon atmosphere. Typically, two n-heptane (spectrographic grade) solutions of 0.2 mol dm -3 sodium bis-(2-ethylhexyl)sulfosuccinate (Aerosol OT, AOT; see Figure 1) were prepared separately in Schlenk tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Meyer et al [63] have generated platinized colloidal cadmium sulfide in situ in AOT based microemulsions. Several studies have recently been published on the synthesis, growth and characterization of cadmium sulfide [64][65][66][67][68][69][70] and cadmium selenide [71] particles in microemulsions.…”
Section: Particle Synthesis In Microemulsionsmentioning
confidence: 99%
“…In the last three decades since their fi rst reports appeared, [1][2][3][4][5] colloidal semiconductor quantum dots (QDs) attracted continuously increasing interest in different fi elds, including photonics [6][7][8][9][10] and optoelectronics. [11][12][13][14] Improving the characteristics and quality of QDs regarding synthetic Figure 1 a, a stable interface between the MeOH solution and the underlying NaCl-QD mixture instead of an instantaneous mixing is crucial for a successful crystallization.…”
Section: Introductionmentioning
confidence: 99%